15N‐ and 2H proteomic stable isotope probing links nitrogen flow to archaeal heterotrophic activity. (20th May 2014) - Justice, Nicholas B.; Li, Zhou; Wang, Yingfeng; Spaudling, Susan E.; Mosier, Annika C.; Hettich, Robert L.; Pan, Chongle; Banfield, Jillian F.
Summary Understanding how individual species contribute to nutrient transformations in a microbial community is critical to prediction of overall ecosystem function. We conducted microcosm experiments in which floating acid mine drainage (AMD) microbial biofilms were submerged – recapitulating the final stage in a natural biofilm life cycle. Biofilms were amended with either 15NH4+ or deuterium oxide (2H2O) and proteomic stable isotope probing (SIP) was used to track the extent to which different members of the community used these molecules in protein synthesis across anaerobic iron‐reducing, aerobic iron‐reducing and aerobic iron‐oxidizing environments. Sulfobacillus spp. synthesized 15N‐enriched protein almost exclusively under iron‐reducing conditions whereas the Leptospirillum spp. synthesized 15N‐enriched protein in all conditions. There were relatively few 15N‐enriched archaeal proteins, and all showed low atom% enrichment, consistent with Archaea synthesizing protein using the predominantly 14N biomass derived from recycled biomolecules. In parallel experiments using 2H2O, extensive archaeal protein synthesis was detected in all conditions. In contrast, the bacterial species showed little protein synthesis using 2H2O. The nearly exclusive ability of Archaea to synthesize proteins using 2H2O may be due to archaeal heterotrophy, whereby Archaea offset deleterious effects of 2H by accessing 1H generated by respiration of organic compounds.